Alveolar Arterial Gradient and Respiratory Index in Predicting the Outcome of COVID-19 Patients; a Retrospective Cross-Sectional Study - Singh, Abhishek; Soni, Kapil Dev; Singh, Yudhyavir; Aggarwal, Richa; Venkateswaran, Vineeta; Ashar, Mohd Suhail; Trikha, Anjan (Archives of Academic Emergency Medicine, 2022)
Introduction: Alveolar arterial (A-a) oxygen gradient and respiratory index can be of immense help for the critical care physician in clinical decision making. This study aimed to evaluate the potential application of A-a oxygen gradient and respiratory index in predicting the survival of COVID-19 patients in intensive care unit (ICU). Method: This is a retrospective cross-sectional study involving 215 adult patients with COVID-19 disease, admitted to the ICU between 1st April 2020 and 30 June 2021. Details regarding demographic variables, comorbidities, laboratory and arterial blood gas (ABG) findings were recorded. Alveolar-arterial gradient and respiratory index were calculated and tested as predictors of survival. Result: The mean age of the patients was 51.92 years (65.6 % male). Hypertension was the most common comorbidity and oxygen via non-rebreathing mask was the most common modality used at the time of ICU admission. Mortality was 28.37% and average length of stay was 12.84 days. Patients who died were older (p=0.02), mostly male (p=0.017), had at least one comorbidity (p<0.001), and higher heart rate and respiratory rate (<0.001 and p=0.03, respectively), lower pH on arterial blood gas (ABG) (p=0.002), higher FiO2 requirement (p<0.001), and increased A-a oxygen gradient on admission compared to survivors. According to receiver operating characteristic (ROC) curve analysis, A-a oxygen gradient and respiratory index were not sensitive or specific in predicting mortality in the studied patient subset. Conclusion: A-a oxygen gradient and respiratory index calculated at time of admission to ICU in patients with COVID-19 were poor predictors of survival.